Pengaruh Kualitas Pelayanan Terhadap Kepuasan Nasabah Tabungan Batara Pada PT. Bank Tabungan Negara (Persero), Tbk Kantor Cabang Manado - Kusame, Krissanto; Tampi, Johny Revo Elia; Tumbel, Tineke M. (JURNAL ADMINISTRASI BISNIS (JAB), 2016)
Abstract : Quality is the expected level of excellence and control over the level of excellence to meet customer desires. Customer satisfaction is the emotional responseof the experiences related to specific products or services purchased, retail outlets, oreven behavioral patterns (such as shopping behavior and the behavior of the buyer),as well as the overall market. This study aims to determine the effect of service quality on customer satisfaction atPT. State Savings Bank, Tbk Branch Manado. This study uses a quantitative descriptive study using Analysis CorrelationCoefficient, Coefficient of Determination / Determinant Coefficient, RegressionAnalysis, Hypothesis Testing To analyze the Influence of Service Quality CustomerSatisfaction Savings Batara PT. BTN (Persero), Tbk Branch Manado The results of this study indicate that the variable quality of service has a stronginfluence on customer satisfaction. keyword: service quality, customer satisfaction